2016
DOI: 10.1056/nejmoa1505180
|View full text |Cite
|
Sign up to set email alerts
|

Eluxadoline for Irritable Bowel Syndrome with Diarrhea

Abstract: Background Effective and safe treatments are needed for patients who have irritable bowel syndrome (IBS) with diarrhea. We conducted two phase 3 trials to assess the efficacy and safety of eluxadoline, a new oral agent with mixed opioid effects (μ- and κ-opioid receptor agonist and δ-opioid receptor antagonist), in patients with IBS with diarrhea. Methods We randomly assigned 2427 adults who had IBS with diarrhea to eluxadoline (at a dose of 75 mg or 100 mg) or placebo twice daily for 26 weeks (IBS-3002 trial)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
374
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(400 citation statements)
references
References 38 publications
18
374
0
2
Order By: Relevance
“…4 Response rates were significantly higher with eluxadoline than placebo after 12 and 26 weeks (p<0.001) (see Figure 1). 3 A response was evident within the first week of treatment and was associated with improved stool consistency and less frequency and urgency. Eluxadoline was associated with greater improvement in abdominal pain and, at the higher dose, reduced bloating.…”
Section: Efficacymentioning
confidence: 96%
See 2 more Smart Citations
“…4 Response rates were significantly higher with eluxadoline than placebo after 12 and 26 weeks (p<0.001) (see Figure 1). 3 A response was evident within the first week of treatment and was associated with improved stool consistency and less frequency and urgency. Eluxadoline was associated with greater improvement in abdominal pain and, at the higher dose, reduced bloating.…”
Section: Efficacymentioning
confidence: 96%
“…The most frequently reported events were constipation (8% with eluxadoline vs 2.5% with placebo), nausea (7.7% vs 5.1%) and abdominal pain (6.5% vs 4.1%). 3 In pooled studies, 1%-2% of patients taking eluxadoline reported somnolence compared with 0.3% taking placebo, but absolute numbers were small. Pancreatitis (two cases at the lower dose of eluxadoline, three at the higher) and sphincter of Oddi spasm (one and seven cases respectively) were reported with eluxadoline but not with placebo.…”
Section: Adverse Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Adult men and women who met Rome III criteria for IBS-D and who had a mean WAP score > 3, mean BSFS ⩾ 5.5, a BSFS ⩾ 5 for at least 5 days, and a mean IBS-D global symptom score of ⩾2 were eligible to participate. Patients were randomized to receive either eluxadoline at a dose of 100 or 75 mg BID or placebo for 26 weeks.…”
Section: Efficacymentioning
confidence: 99%
“…The clinical trial data for eluxadoline are also being submitted to other global health and medicines authorities (namely EMA). [40,41,48] …”
Section: Safety and Tolerabilitymentioning
confidence: 99%